Post-traumatic Superior Sagittal Sinus Thrombosis - Mukherji, JD; Sen, KK; Singh, Prakash; Singh, KK (Indian Journal of Neurotrauma, 2004)
Cerebral sinus venous thrombosis (CVST) is a rare complication following head injury. The diagnosis may remain elusive and consequently the outcome grave unless high index of suspicion coupled with magnetic resonance imaging (MRI) and magnetic resonance venography (MRV) is resorted to at an early stage. We report two cases CVST following head injury.
Keywords: cerebral venous sinus thrombosis; head injury